Bitcoin una fuente de inversión en tiempos de crisis económica: estudio empírico en la ciudad de Loja, periodo 2020-2021 - Luzuriaga Herrera, Sonia Paola (2022)
The undoubted evolution of the financial market, as well as the technological development, has allowed the inclusion of new investment alternatives and unconventional money-exchange systems. Some of them are regulated by control entities, while others, such as Bitcoin, are decentralized in nature. This research focuses on Bitcoin cryptocurrency as an investment alternative in times of financial crisis. To achieve the objectives, bibliographical research was carried out by gathering information from magazines, books, academic papers, and the current Monetary Law. Likewise, a survey-type instrument was applied to collect data. The survey consists of seventeen questions to know the operation of cryptocurrency, people’s cryptocurrency approval in Loja, and the investor’s profile. In addition, a didactic guide was developed based on the models proposed by Coinmotion (2019) and Lizano y Barrantes (2019). Regarding the results, it can be pointed out that there is not a regulatory framework for Bitcoin in the country. Concerning the use of this cryptocurrency, its use in Loja is minimal. The didactic guide with fundamental information about cryptocurrency is provided so the population can expand their knowledge about it and subsequently make decisions.